What are the effects of Agro-Ecological Zones and land use region boundaries on land resource projection using the Global Change Assessment Model?. (November 2016) - Di Vittorio, Alan V.; Kyle, Page; Collins, William D.
Abstract: Understanding potential impacts of climate change is complicated by spatially mismatched land representations between gridded datasets and models, and land use models with larger regions defined by geopolitical and/or biophysical criteria. Here we quantify the sensitivity of Global Change Assessment Model (GCAM) outputs to the delineation of Agro-Ecological Zones (AEZs), which are normally based on historical (1961–1990) climate. We reconstruct GCAM's land regions using projected (2071–2100) climate, and find large differences in estimated future land use that correspond with differences in agricultural commodity prices and production volumes. Importantly, historically delineated AEZs experience spatially heterogeneous climate impacts over time, and do not necessarily provide more homogenous initial land productivity than projected AEZs. We conclude that non-climatic criteria for land use region delineation are likely preferable for modeling land use change in the context of climate change, and that uncertainty associated with land delineation needs to be quantified. Highlights: Land resource inputs and projections are sensitive to land use region boundaries. Developed a system to generate land data for given Agro-Ecological Zones (AEZs). AEZs based on projected climate differ considerably from historical AEZs. Climate within historical AEZs becomes spatially heterogeneous with climate change. Non-climatic land use region boundaries may reduce model error, compared to AEZs.